Novel approach towards the synthesis of highly efficient flame retardant electrode and oil/organic solvent absorber. (May 2020) - Khose, Rahul V.; Wadekar, Pravin H.; Pethsangave, Dattatray A.; Chakraborty, Goutam; Ray, Alok K.; Some, Surajit
Abstract: We have developed a facile one pot process to synthesize an ultra-light functionalized spongy graphene (FSG). This is the first approach to use carbon based flame retardant spongy material as an electrode to build completely flame retardant supercapacitor (FRS) also as an oil/organic solvent absorber. The fully FRS concept has created by the compilation of as-prepared FSG with flame retardant separator and electrolyte. As-prepared FSG contained high amount of phosphorus and nitrogen functional groups, which makes it potent flame retardant electrochemical material, to use it as an efficient FR electrode. Flame test of FSG revealed that it doesn't catch fire for ∼1500 s. Also, FSG was able to sustain flame retardancy at a temperature as high as 1500 °C for continuous exposure of ∼300 s. FSG used as an electrode for symmetric capacitor possessing maximum specific capacitance of 494.3 F g −1 at a current density 1 A g −1 . Corresponding high energy density and power density values are 55.6 Wh kg −1 and 1799 W kg −1 . It shows cycling stability of 86.1% after 5000 cycles at current density of 10 A g −1 . The electrochemical property of FSG was also confirmed using three electrode system. Flame retardant FSG material was also used for the absorption and recovery of oil and organic solvents. FSG has high oil and organic solvent sorption capacity in the range of 40–70 g/g, also can be reused for minimum 10 cycles. Such approach has great significance for multifunctional graphene based nanocomposites will open the new window for large-scale applications. Graphical abstract: Image 1 Highlights: Prepared an ultra-light functionalized flame retardant spongy graphene (FSG). FSG can sustain in high temperature of 1500 °C for ∼300 s. FSG shows specific capacitance of 493.3 F g −1 at current density 1 A g −1 . FSG shows oil and organic solvent sorption capacity in range of 40–70 g/g.